139k views
3 votes
Let f(x) = -­2x ­- 7 and g(x) = ­-4x + 3. Find (fog)(-­5)

User Gargamel
by
5.1k points

1 Answer

1 vote

ANSWER


( f \circ \: g)( - 5)= -53

Step-by-step explanation

The given functions are:

f(x) = -­2x ­- 7 and g(x) = ­-4x + 3


( f \circ \: g)(x) = f(g(x))


( f \circ \: g)(x) = f( - 4x + 3)


( f \circ \: g)(x) = - 2( - 4x + 3) - 7

Expand:


( f \circ \: g)(x) = 8x - 6 - 7


( f \circ \: g)(x) = 8x - 13

We substitute x=-5


( f \circ \: g)( - 5) = 8( - 5) - 13 = -53

User David Carmo
by
4.9k points